2020
DOI: 10.24996/ijs.2020.61.5.9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of EBV on Multiple in a Sample of Iraqi Females: Immunological and Molecular Study

Abstract: This study was designed to highlight the role of Epstein Barr viruses (EBV) as a possible causative effect in multiple sclerosis (MS) through testing the viral load along with both biochemical and immunological parameters in female MS patients. We also aimed at finding the effects of different types of treatment line on the various study aspects. The results of the enzyme-linked immunosorbent assay (ELISA) revealed first an increased level of EBV EBNA1IgG IL-17A (96.13±27.60 pg/ml) in sera of female MS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
(37 reference statements)
2
9
0
Order By: Relevance
“…The significantly higher seropositivity of EBNA-1 IgG in the MS patients than in the controls is in accordance with other studies (20,21) , however, other studies, (Banwell et al, 2007), which was carried out on children, failed to manifest any relationship between the virus and MS (22) . The median level of EBNA-1 IgG for MS patients and controls were 81.08 U/ml and 67.73 U/ml respectively, which was significantly higher in MS patients in the current study, as reported by other studies which have showed significantly higher IgG level in MS patients (10,11,23,24) , while others found no significant difference (25,26) . Concerning the association between EBNA-1 IgG results and duration of MS disease, the current study revealed higher serum level and seropositivity of EBNA-1 IgG in MS patients during first two years of disease and this result is in accordance with other study (11) , this is indicative of the role of the viral antigen in the early stages of the disease which could be the triggering factor of MS. And due to this triggering factor, the relationship linking EBNA-1 IgG titers and number of clinical relapses showed no statistically significant association as shown in the table (5), this result is close to what's mentioned by Bakir et al in 2017 (10) .…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The significantly higher seropositivity of EBNA-1 IgG in the MS patients than in the controls is in accordance with other studies (20,21) , however, other studies, (Banwell et al, 2007), which was carried out on children, failed to manifest any relationship between the virus and MS (22) . The median level of EBNA-1 IgG for MS patients and controls were 81.08 U/ml and 67.73 U/ml respectively, which was significantly higher in MS patients in the current study, as reported by other studies which have showed significantly higher IgG level in MS patients (10,11,23,24) , while others found no significant difference (25,26) . Concerning the association between EBNA-1 IgG results and duration of MS disease, the current study revealed higher serum level and seropositivity of EBNA-1 IgG in MS patients during first two years of disease and this result is in accordance with other study (11) , this is indicative of the role of the viral antigen in the early stages of the disease which could be the triggering factor of MS. And due to this triggering factor, the relationship linking EBNA-1 IgG titers and number of clinical relapses showed no statistically significant association as shown in the table (5), this result is close to what's mentioned by Bakir et al in 2017 (10) .…”
Section: Resultssupporting
confidence: 86%
“…On the other hand, in this study, patients with the first-line and second-line treatment showed no significant differences in EBNA 1 IgG levels between each other, while the median level in patients without treatment were higher, this result is comparable to result of study carried out by Abd Al Kareem and Abd in 2020 (11) , these patients who were recently diagnosed with MS had very high median IgG titer also supporting the possible triggering factor by the viral antigen.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Sore throat is a common presentation in pediatric office settings and emergency departments Bacterial infection due to Streptococcus pyogenes represented about 25% of sore throat in children ( Abd Al-Kareem et al, 2014). This a major human-specific bacterial pathogen that causes a wide array of manifestations ranging from mild localized infections to life-threatening invasive infections (Hadi et al,2017).…”
Section: Introductionmentioning
confidence: 99%